Securing the IoT frontier: exploring the limitation and future directions in cybersecurity - Mahmoud Ahmed, Moustafa Abdelrahman; Md Yunus, Nur Arzilawati (The Institute of Internet, Broadcasting and Communication, 2024)
As the Internet of Things (IoT) continues to permeate every facet of modern life, the imperative to secure this vast and dynamic frontier becomes increasingly paramount. This presents a comprehensive exploration of the challenges and opportunities inherent in safeguarding the interconnected web of IoT devices. The research critically examines the limitations of current cybersecurity measures through an extensive review of diverse topics, including IoT network performance, smart grid security, and the escalating cyber threats against critical infrastructures. A meticulous analysis of research findings underscores the need for enhanced infrastructure and ongoing research to fortify the cybersecurity mechanisms surrounding IoT objects. We underline the imperative of relentless research efforts to parry the advancing threats and leverage the promise of nascent technologies. Our findings affirm the pivotal influence of robust cybersecurity measures in crafting a resiliently connected ecosystem. The paper underscores the importance of ongoing research to address evolving threats and harness the potential of emerging technologies, reaffirming the central role of cybersecurity in shaping a secure interconnected world. In conclusion, the study emphasizes the dynamic and ever-evolving nature of cybersecurity on the IoT frontier. It unveils a complex landscape of challenges, ranging from network performance intricacies to the security concerns of critical infrastructures.